A census of the Icelandic Whooper Swan population - Gardarsson, Arnthor; Skarphedisson, Kristinn H (Wildfowl, 1984)
A total of 9057 Whooper Swans Cygnus cygnus were found in a census covering most staging areas in Iceland in October 1982. About 850-1400 may have been missed in Iceland and 200-500 in the British Isles. Thus the total Icelandic population was between 10,000 and 11,000. About 18% of the number were young of the year. The percentage of young in October varied between parts of Iceland, largely as a result of the distribution of flocks of moulting non-breeders. The mean brood size was 2.60. Significant brood reduction occurred in August-September but after that there was good survival. Migration did not appear to increase juvenile mortality and the proportion of young did not change during winter 1982-3, suggesting that survival of juveniles was similar to that of older birds. Surveys in 1971-83 indicate that about 6200 full grown Whoopers moult in flocks, mainly on saline waters. A shift to freshwaters and of breeders from high ground to the lowlands takes place in autumn. An outline model of the population which fits available census data is presented (Table 8).